Estımatıon of hypersonıc unsteady and qausı-steady dampıng derıvatıves for a delta wings at large incıdence - Renita, sharon Monis; Crasta, Asha; Khan, Sher Afghan (Science and Engineering Research Support Society, 2020)
This paper presents results of quasi-steady and unsteady damping derivatives of a delta wing whose leading edge is straight. Results are computed for a wide range of Mach numbers and angles of attack. Here the contribution to the damping derivatives due to the rate of change of angle of attack is estimated separately. The results show that with the increase in Mach number, there is a progressive decrease in the damping derivatives for both the cases (i.e., unsteady and quasi-steady). With the further rise in the Mach values, the magnitude of decline has diminished for Mach number M = 10 and above the state of steady-state is achieved. For the entire range of the Mach number, the location of the center of pressure remained unchanged for a fixed value of the flow deflection angle δ. For the lower flow deflection angle of the wing, the magnitude of the damping derivatives is smaller as compared to the higher values of δ. The contribution to the damping derivatives from the rate of change of angle of attack is around 20 percent of the quasi-steady one. The results for flow deflection angles of ten degrees and twenty degrees show a different trend. When we compare the results of the damping derivatives for a fixed pivot position, it is seen that the damping derivatives show different behavior for two different values of the flow deflection angle δ. The steady-state varies for two values of δ. When we look at the damping derivatives at hinge point k = 0.6, the magnitude is small. The steady-state is attained early for quasi-steady in comparison to the unsteady damping derivatives.